(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2020)
In late 2019 and early 2020 the coronavirus Covid-19 spread rapidly throughout the world, resulting in national lockdowns and extreme anxiety as supermarket stock became sparse and health services were pushed beyond capacity. Amidst the panic buying on the ground and failures to react appropriately at the UK Government level, a wealth of community-run initiatives rapidly developed throughout Scotland, the U.K., and beyond. Newly motivated and seasoned community organisers quickly established Facebook Groups and appropriately-named Twitter hashtags that sought to identify those with the means, health, capacity, and time to help others suddenly faced with unemployment, homelessness, and either self-imposed or healthcare sector recommended isolation and quarantining. During this time, an organisation for whom I am the sole paid and part-time employee, the Tollcross Community Action Network (TCAN), has sought to sustain our weekly Community Hub (operated in partnership with the Tollcross Foodbank) for as long as possible, continuing our frontline support for those living in social or economic isolation, experiencing food poverty, or in need of assistance in understanding medical correspondence or bills. This article briefly describes the struggles, support, and lessons we learnt during the early days of the Covid-19 pandemic.